Faktor-faktor yang Mempengaruhi Audit Judgment: Studi Empiris Big Four di Jakarta - Ignatius Edward Riantono (Universitas Swadaya Gunung Jati, 2018)
AbstractThis study aims to examine the effect of the complexity of audit assignments, audit work experience, perceptions of auditor professional ethics, audit skills, and gender differences in audit judgment both partially and simultaneously. The data used in this study is the primary data. Data obtained through a questionnaire that was answered in full by respondents from KAP The Big Four in Jakarta in 2015. The sampling method used was purposive sampling. The research method used is regression analysis multiple linear processed with SPSS 20.0 for windows with level of significance of 5%. The results of this study indicate that partially there are 3 variables that can influence audit judgment namely audit work experience, perceptions of auditor professional ethics, and gender differences as well as simultaneously complexity of audit assignments, audit work experience, perception of professional ethics auditors, audit skills, and gender differences, can influence audits judgment.Keywords: Experience; Perceptions of professional ethics; Skills; Gender difference; Judgment AbstrakPenelitian ini bertujuan untuk menguji pengaruh kompleksitas penugasan audit, pengalaman kerja audit, persepsi etika profesional auditor, kemahiran audit, dan perbedaan gender terhadap audit judgment baik secara parsial maupun simultan. Data yang digunakan dalam penelitian ini adalah data primer. Data diperoleh melalui kuesioner yang dijawab lengkap oleh responden dari KAP The Big Four di Jakarta pada tahun 2015. Metode pengambilan sampel yang digunakan adalah purposive sampling. Metode penelitian yang digunakan adalah analisis regresi linear berganda yang diolah dengan SPSS 20.0 for windows dengan level of significance 5%. Hasil penelitian ini menunjukkan bahwa secara parsial terdapat 3 variabel yang dapat mempengaruhi audit judgment yaitu pengalaman kerja audit, persepsi etika profesional auditor, dan perbedaan gender serta secara simultan kompleksitas penugasan audit, pengalaman kerja audit, persepsi etika professional auditor, kemahiran audit, dan perbedaan gender, dapat mempengaruhi audit judgment.Kata kunci: Pengalaman kerja; Persepsi etika profesional; Kemahiran; Perbedaan gender; Audit judgment